The Impact of Meditation Practice on Teachers’ Personal and Professional Lives - Qamaniq-Mason, Mary Clarissa (Université d'Ottawa / University of Ottawa, 2018)
This narrative study of schoolteachers’ experiences of yogic meditation employs the theoretical framework of yoga. It poses the research question: How do teachers story their life experiences following their adoption of a regular meditation practice? Narrative research methods are used to reveal the participants’ own perceptions of their experiences of meditation. The narratives presented include that of an educator and meditation teacher who has been practising yogic meditation for over 40 years, as well as three schoolteachers who more recently came to the practice of meditation and were experienced classroom teachers before and after taking up this practice. The findings reveal that (1) the teachers perceive their meditation practice to have a beneficial impact on their lives, and by extension their work as teachers; (2) the impact their meditation practice has on their classroom teaching may not be obvious to an outside observer. Instead it is experienced by the participants to be an internal enrichment: a transformation of their thought patterns and perceptions of feelings and events; and (3) the longer the participant has been practising meditation, and the more they have immersed themselves in the philosophical study that traditionally accompanies yogic practice, the more complex may be their understandings of their meditation experience. This research also highlights the problems with imposing Western knowledge frameworks on practices that have traditionally been accompanied by an existent theoretical framework. The researcher argues for further study of classical yogic meditation practices in light of their potential benefits for educators, with the caveat that such research should be undertaken by researchers who have experienced authentic immersion in the study of yoga and its classical philosophies.
Keywords: Meditation; Yoga; Wellness; Teachers; Stress; Narrative